2022
DOI: 10.1371/journal.pone.0279116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guideline adherence in oncology: A qualitative study of insights from clinicians in Australia

Abstract: Background The burden of cancer is large in Australia, and rates of cancer Clinical Practice Guideline (CPG) adherence is suboptimal across various cancers. Methods The objective of this study is to characterise clinician-perceived barriers and facilitators to cancer CPG adherence in Australia. Semi-structured interviews were conducted to collect data from 33 oncology-focused clinicians (surgeons, radiation oncologists, medical oncologists and haematologists). Clinicians were recruited in 2019 and 2020 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 90 publications
1
17
0
Order By: Relevance
“…GRT was associated with increased survival rates for patients with breast cancer, 66 DLBCL, 69 lung cancer, 54,118 cervical cancer, 59 and colon cancer. 62 Of the 20 studies included in this review, 15 39 This supports the need for further generation of real-world data 76 to build the evidence base to guide cancer treatments for older patients, those with later stage disease and comorbidities, in addition to the healthier and younger patients typically included in clinical trials. 38 Low SES was associated with poor GRT in lung cancer 57,118 ; however, the opposite was true for stages B and C rectal cancer patients, potentially as a result of patient preference, or clinical factors that influence treatment decisions.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…GRT was associated with increased survival rates for patients with breast cancer, 66 DLBCL, 69 lung cancer, 54,118 cervical cancer, 59 and colon cancer. 62 Of the 20 studies included in this review, 15 39 This supports the need for further generation of real-world data 76 to build the evidence base to guide cancer treatments for older patients, those with later stage disease and comorbidities, in addition to the healthier and younger patients typically included in clinical trials. 38 Low SES was associated with poor GRT in lung cancer 57,118 ; however, the opposite was true for stages B and C rectal cancer patients, potentially as a result of patient preference, or clinical factors that influence treatment decisions.…”
Section: Discussionmentioning
confidence: 77%
“…Recent research has identified perceived barriers (such as outdated recommendations) and facilitators (such as multidisciplinary peer review) to cancer treatment CPG adherence in Australia, 39 and internationally, 38 and demonstrated that clinician adherence to CPGs is influenced by a multitude of factors, including the quality of CPG development, frequency of updates, patient, clinician and organizational factors, as well as dissemination, and implementation strategies 38,39,74 . These findings add texture by highlighting CPG adherence factors specific to various cancer streams, and in combination, these local contextual factors will inform cancer treatment CPG implementation strategies to address the barriers specific to CPG adherence in Australia, as guided by the Knowledge to Action framework 75 or other implementation frameworks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be challenges to care pathway implementation [ 24 – 29 ]. We included an interprofessional review stage in our procedures to facilitate implementation.…”
Section: Discussionmentioning
confidence: 99%